2012
DOI: 10.1021/la303828s
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Formation of Thiol and Disulfide Interfaces

Abstract: The work reported herein describes the controlled creation of uniform thiol-functionalized siloxane-anchored self-assembled monolayers (SAMs) and their selective transformation into intramonolayer (bridging) disulfides. These disulfides provide for the efficient immobilization of (bio)molecules bearing pendant thiols or disulfides, with no need for added oxidant. The unambiguous development of this surface chemistry required analytical methods that distinguish thiol and disulfide moieties on a surface. Physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Ionic interactions in polymers are primarily manifested by the formation of ionomers, [93] and selected polymers demonstrated self-healing attributes. For example, in poly(ethylene-co-methacrylic acid) (EMAA) shown in Figure 10 sheets can be surface modified to generate amine, [116] carboxylic acid, [117] hydroxyl, [118] UPy, [119] thiol, [120] furfuryl, [121] cinnamoyl, [122] anthracene, [123] or pyrenyl groups [124], which can react with their counterparts in the matrix. Thus, the nature of modifications will be determined by the polymer motif to form reversible bonds with a polymer matrix.…”
Section: Ionic Interactionsmentioning
confidence: 99%
“…Ionic interactions in polymers are primarily manifested by the formation of ionomers, [93] and selected polymers demonstrated self-healing attributes. For example, in poly(ethylene-co-methacrylic acid) (EMAA) shown in Figure 10 sheets can be surface modified to generate amine, [116] carboxylic acid, [117] hydroxyl, [118] UPy, [119] thiol, [120] furfuryl, [121] cinnamoyl, [122] anthracene, [123] or pyrenyl groups [124], which can react with their counterparts in the matrix. Thus, the nature of modifications will be determined by the polymer motif to form reversible bonds with a polymer matrix.…”
Section: Ionic Interactionsmentioning
confidence: 99%
“…Figure shows a bulk plasmon band from a bare silicon substrate covered with native silicon oxide without apparent sulfur peak (S 2p). In the XPS spectra of the MPTES layer, the sulfur peak (S 2p) was detected at 163.7 eV, which indicated that all of the sulfur was present as thiol or disulfide . XPS was also used to study the composition of disulfide bridge after immobilization of DNA oligonucleotides.…”
Section: Resultsmentioning
confidence: 99%
“…2, see appendix). Acetyl removal is monitored by infra-red spectroscopy based on the disappearance of the characteristic C = O double bond signal [30,31]. Subsequent processing depends on the specific substrates to be bonded and the two bonding paradigms that have been pursued.…”
Section: Monolayer-assisted Bonding Of Silicon-to-inp and Silicon-to-mentioning
confidence: 99%
“…The bonding of a thiol-SAM-modified silicon wafer to such a disulfide-bearing surface is based on a disulfide exchange reaction in which the intra-SAM S-S bonds of the disulfide surface are opened by reaction with a thiol-decorated monolayer to form new disulfide bonds across the interface (see Fig. 5(b)) [25,31]. Figure 5(c) shows a pair of silicon samples bonded using this process.…”
Section: Monolayer-assisted Bonding Of Silicon-to-inp and Silicon-to-mentioning
confidence: 99%
See 1 more Smart Citation